Compromised NLRP3 and AIM2 inflammasome function in autoimmune NZB/W F1 mouse macrophages. Issue 1 (19th August 2018) - Thygesen, Sara J; Takizawa, Karli E; Robertson, Avril A B; Sester, David P; Stacey, Katryn J
Abstract: Inflammasomes are protein complexes activated by infection and cellular stress that promote caspase‐1 activation and subsequent inflammatory cytokine processing and cell death. It has been anticipated that inflammasome activity contributes to autoimmunity. However, we previously showed that macrophages from autoimmune New Zealand Black (NZB) mice lack NLRP3 inflammasome function, and their absent in melanoma 2 (AIM2) inflammasome responses are compromised by high expression of the AIM2 antagonist protein p202. Here we found that the point mutation leading to lack of NLRP3 expression occurred early in the NZB strain establishment, as it is shared with the related obese strain New Zealand Obese, but not with the unrelated New Zealand White (NZW) strain. The first cross progeny of NZB and NZW mice develop more severe lupus nephritis than the NZB strain. We have compared AIM2 and NLRP3 inflammasome function in macrophages from NZB, NZW, and NZB/W F1 mice. The NZW parental strain showed strong inflammasome function, whereas the NZB/W F1 have haploinsufficient expression of NLRP3 and show reduced NLRP3 and AIM2 inflammasome responses, particularly at low stimulus strength. It remains to be established whether the low inflammasome function could contribute to loss of tolerance and the onset of autoimmunity in NZB and NZB/W F1. However, with amplifying inflammatory stimuli through the course of disease, the NLRP3 response in the NZB/W F1 may be sufficient to contribute to kidney damage at later stages of disease. Abstract : Lupus‐prone NZB mice have no NLRP3 expression and low absent in melanoma 2 (AIM2) function, questioning the role of inflammasomes in autoimmunity. The first cross progeny of New Zealand Black (NZB) and New Zealand White mice (NZB/W F1) develop autoimmunity with more severe lupus nephritis than NZB, and their macrophages have partially compromised NLRP3 and AIM2 inflammasomes. The residual activity may be sufficient to contribute to nephritis. However, suboptimal inflammasome function could also contribute to loss of tolerance in early disease.